228k views
5 votes
Question 10 of 12, Step 1 of 27/15CorrectGiven two functions/) and (c):/() = 3x2 + 4, 8(x) = 3x - 2Step 1 of 2: Form the composition (g)(x).Answer(g)(x) =

Question 10 of 12, Step 1 of 27/15CorrectGiven two functions/) and (c):/() = 3x2 + 4, 8(x-example-1
User Diepie
by
4.8k points

1 Answer

4 votes

Given the following functions:


\begin{gathered} f(x)=3x^2+4 \\ g(x)=3x-2 \end{gathered}

We will form the composition ( f o g)(x)

So, substitute with the function (g) into the function (f)


(f\circ g)(x)=3(3x-2)^2+4

Simplify the expression:


\begin{gathered} (f\circ g)(x)=3(9x^2-12x+4)+4 \\ (f\circ g)(x)=27x^2-36x+12+4 \\ \\ (f\circ g)(x)=27x^2-36x+16 \end{gathered}

So, the answer will be;


(f\circ g)(x)=27x^(2)-36x+16

User Locoboy
by
5.3k points